2012
DOI: 10.3390/su4123302
|View full text |Cite
|
Sign up to set email alerts
|

Local Perceptions and Responses to Climate Change and Variability: The Case of Laikipia District, Kenya

Abstract: Agricultural policies in Kenya aim to improve farmers' livelihoods. With projected climate change, these policies are short of mechanisms that promote farmers' adaptation. As a result, smallholders are confronted with a variety of challenges including climate change, which hinders their agricultural production. Local knowledge can be instrumental in assisting smallholders to cope with climate change and variability. In this paper, we present empirical evidence that demonstrates local knowledge, perceptions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
84
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 46 publications
(65 reference statements)
15
84
1
2
Order By: Relevance
“…Anyway, coping strategies were implemented to respond to these constraints. The findings of this study are in agreement with those of Ogalleh et al (2012) in his work on Local Perceptions and Responses to Climate Change and Variability in Kenya. He reported that most farmers preferred multiple options, based on adaptation practices involving diversification and use of various crop varieties.…”
Section: Farmer's Perception Of Risk and Uncertainty In Climatesupporting
confidence: 82%
“…Anyway, coping strategies were implemented to respond to these constraints. The findings of this study are in agreement with those of Ogalleh et al (2012) in his work on Local Perceptions and Responses to Climate Change and Variability in Kenya. He reported that most farmers preferred multiple options, based on adaptation practices involving diversification and use of various crop varieties.…”
Section: Farmer's Perception Of Risk and Uncertainty In Climatesupporting
confidence: 82%
“…Research on understanding local perceptions of climate variability and its impacts is important for supporting the development of climate change adaptation policy at the local scale [21]. Agricultural livelihoods are dependent on the weather, therefore farmers pay attention to the variability of local weather and climate, and indeed they tend to notice changes.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The livelihood systems of small-scale farmers in this region have been studied intensively for more than 20 years [18][19][20][21][22][23]. However, to date, there is only little spatially explicit quantitative information on agricultural expansion and land use intensification in the region, if any at all.…”
Section: Introductionmentioning
confidence: 99%